Research trends in Islam and Sustainable Development based on Scopus data using R Studio and Vos Viewer: Bibliometric Analysis - Hoya, Ade Lenty; Irman Jaya , La Ode; Abidin, Jaenal; Haris , Amnan (WISE Pendidikan Indonesia, 2025)
Islam has principles that support sustainable development, such as responsibility for protecting nature, social justice and balance. Despite its relevance to the Sustainable Development Goals (SDGs), the link between Islam and sustainable development has been less explored in academic research. Therefore, further research is needed to analyze the trends and sparse research on Islam in supporting global efforts to achieve sustainability. This study aims to look at publications over the last ten years and to find novelty or research trends as well as research that is still rarely done. The method used is literature review through scopus data and analyzed using VOSviewer© dengan R Studio. The bibliometric analysis on Islam and Sustainable Development found 211 documents (2014-2024), with a peak of publications in 2022 (31 articles). The most relevant source was Iop Conference Series with 17 articles. Hassan R was the most prolific author (4 articles), and Universiti Sains Malaysia was the main affiliation. The most cited article came from Murphy Mj (2020) with 55 citations, while the US had the most citations (104). Malaysia leads in scientific production with 119 publications. Major trends related to this topic include planning, information management, and economic and social effects, while areas related to health and demographics are less researched.